Contribution Of Environment, Social, Governance And Financial Performance To Firm Value - Zakky Rudy Anggara; Ira Wikartika (Universitas Trunodjoyo Madura, 2025)
Firm value reflects how effectively a company manages its assets to attract investors. Amid rising sustainability concerns, Environmental, Social, and Governance (ESG) practices have become a focal point, as their adoption is expected to bolster firm value. The government has likewise supported this trend by introducing regulations on sustainability. However, many firms still fall short in implementing these practices optimally, sometimes even causing negative environmental and social consequences. Furthermore, robust financial performance must now be accompanied by transparent disclosure of sustainability information. This study investigates the influence of ESG disclosure, profitability, and liquidity on firm value in the sustainability era. Using a quantitative methodology, it analyzes a purposive sample of twelve energy-sector companies listed on the Indonesia Stock Exchange over the 2021–2023 period. The findings reveal that neither ESG disclosure nor liquidity has a significant influence on firm value, whereas profitability demonstrates a strong positive effect.